2021
DOI: 10.3390/ma14051321
|View full text |Cite
|
Sign up to set email alerts
|

Particle Characteristics’ Influence on FLASH Sintering of Potassium Sodium Niobate: A Relationship with Conduction Mechanisms

Abstract: The considerable decrease in temperature and time makes FLASH sintering a more sustainable alternative for materials processing. FLASH also becomes relevant if volatile elements are part of the material to be processed, as in alkali-based piezoelectrics like the promising lead-free K0.5Na0.5NbO3 (KNN). Due to the volatile nature of K and Na, KNN is difficult to process by conventional sintering. Although some studies have been undertaken, much remains to be understood to properly engineer the FLASH sintering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Despite its simplicity, FS is an extremely powerful sintering method that can be successfully used for most ceramic materials, from dielectrics (BaTiO 3 [41][42][43][44][45][46][47] or (Bi 0.2 Na 0.2 K 0.2 Ba 0.2 Ca 0.2 )TiO 3 [48]) to ionic (Zirconia, YSZ [2,[49][50][51][52], CeO 2 or doped-CeO 2 [53][54][55][56][57][58]) or electronic (TiO 2 [19,22,[59][60][61][62], BiFeO 3 or substituted-BiFeO 3 [24,27]) conductors. Interestingly, it can be also applied for processing ceramic composites of complex stoichiometry, metastable phases, or materials constituted by volatile species at the temperatures required for their sintering such as YSZ-Al 2 O 3 composites [63][64][65], different types of solid state electrolytes [25,66,67], BiFeO 3 [68,69], or K 0.5 Na 0.5 NbO 3 [26,[70][71][72][73]. Moreover, ceramics prepared by FS present very interesting properties rarely reported for materials obtained by convectional procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its simplicity, FS is an extremely powerful sintering method that can be successfully used for most ceramic materials, from dielectrics (BaTiO 3 [41][42][43][44][45][46][47] or (Bi 0.2 Na 0.2 K 0.2 Ba 0.2 Ca 0.2 )TiO 3 [48]) to ionic (Zirconia, YSZ [2,[49][50][51][52], CeO 2 or doped-CeO 2 [53][54][55][56][57][58]) or electronic (TiO 2 [19,22,[59][60][61][62], BiFeO 3 or substituted-BiFeO 3 [24,27]) conductors. Interestingly, it can be also applied for processing ceramic composites of complex stoichiometry, metastable phases, or materials constituted by volatile species at the temperatures required for their sintering such as YSZ-Al 2 O 3 composites [63][64][65], different types of solid state electrolytes [25,66,67], BiFeO 3 [68,69], or K 0.5 Na 0.5 NbO 3 [26,[70][71][72][73]. Moreover, ceramics prepared by FS present very interesting properties rarely reported for materials obtained by convectional procedures.…”
Section: Resultsmentioning
confidence: 99%
“…An inner working atmosphere is not a prerequisite either, but indeed it is possible to tune it to study its effect over the final properties of the material [14,19,20]. Moreover, some flashsintered materials have been granted special properties [21,22] and it has been shown that it is possible to sinter unstable oxides with volatile components and complex composition while preserving their stoichiometry and properties [23][24][25][26]. Very recently, in 2018, it was reported that sintering and synthesis can be merged into a single step, giving rise to what has been named Reaction or Reactive Flash Sintering (RFS) and constitutes [27], by itself, another important branch of research.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, current flow through grain boundaries (GBs) was proposed as the governing mechanism for FS of KNN, causing amorphization and particle sliding. 22 However, there is no consensus on how FS occurs in KNN in particular, as is the case for a plethora of other ceramics. 21,[23][24][25] Above all, there are no reports of FS of KNN that resulted in sintered density well above 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies showed the possibility of FS KNN ceramics (dog bone specimen shape) in 30 s at 990°C to 94 % theoretical density under 50 V/cm and 20 mA/mm 2 20 . A core‐shell structure was postulated to form that is based on Na and K, leading to preferential heating at particle surfaces and Na volatilization 22 . Recently, current flow through grain boundaries (GBs) was proposed as the governing mechanism for FS of KNN, causing amorphization and particle sliding 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation